2008
DOI: 10.1093/molbev/msn100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Exchange versus Genetic Differentiation in a Medium-Sized Inversion of Drosophila: The A2/Ast Arrangements of Drosophila subobscura

Abstract: Chromosomal inversion polymorphism affects nucleotide variation at loci associated with inversions. In Drosophila subobscura, a species with a rich chromosomal inversion polymorphism and the largest recombinational map so far reported in the Drosophila genus, extensive genetic structure of nucleotide variation was detected in the segment affected by the O(3) inversion, a moderately sized inversion at Muller's element E. Indeed, a strong genetic differentiation all over O(3) and no evidence of a higher genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…Actually, a number of studies (for example Aguadé, 1988;Aguadé, 1990, 1994;Aquadro et al, 1991;Benassi et al, 1993;Popadic et al, 1995;Babcock and Anderson, 1996;Hasson and Eanes, 1996;Rozas et al, 1999;Schaeffer et al, 2003;Nobrega et al, 2008;Kulathinal et al, 2009 and others) have shown extensive genetic differentiation between gene arrangements, a pattern that is consistent with the reduction of recombination levels expected in inversion heterozygotes (Roberts, 1976). Still, there is evidence of genetic exchange (either by gene conversion or double crossover) between gene arrangements Aguadé 1990, 1994;Rozas et al, 1999;Schaeffer and Anderson, 2005).…”
Section: Introductionmentioning
confidence: 69%
“…Actually, a number of studies (for example Aguadé, 1988;Aguadé, 1990, 1994;Aquadro et al, 1991;Benassi et al, 1993;Popadic et al, 1995;Babcock and Anderson, 1996;Hasson and Eanes, 1996;Rozas et al, 1999;Schaeffer et al, 2003;Nobrega et al, 2008;Kulathinal et al, 2009 and others) have shown extensive genetic differentiation between gene arrangements, a pattern that is consistent with the reduction of recombination levels expected in inversion heterozygotes (Roberts, 1976). Still, there is evidence of genetic exchange (either by gene conversion or double crossover) between gene arrangements Aguadé 1990, 1994;Rozas et al, 1999;Schaeffer and Anderson, 2005).…”
Section: Introductionmentioning
confidence: 69%
“…In comparison, the double-crossover rate across similar regions in homokaryotypes is approximately 5–10% (Gruneberg 1935; Spurway and Philip 1952; Novitski and Braver 1954; Robbins 1974; Pegueroles et al 2010), showing that double-recombination products are not produced as frequently as expected in inversion heterozygotes. Sequencing approaches have enhanced our understanding of differentiation within inverted regions by being able to detect double-crossover events or historical gene flux due to conversion within an inverted region (Rozas and Aguade 1994; Wesley and Eanes 1994; Hasson and Eanes 1996; Betran et al 1997; Laayouni et al 2003; Schaeffer and Anderson 2005; Nobrega et al 2008; White et al 2009). These studies confirm predictions by theoretical models for flux rates to be highest near the center of inverted regions (Navarro et al 1997; Kirkpatrick and Barton 2006; Feder and Nosil 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Inversion-induced LD has been reported in a variety of organisms, including humans (Bansal et al 2007), Drosophila subobscura (Munte et al 2005), and several other species (reviewed in Hoffmann and Rieseberg 2008). Strong differentiation between chromosomal arrangements (as measured by F ST ) has also been used as evidence of inversions in Drosophila (Andolfatto et al 1999;Depaulis et al 1999;Nóbrega et al 2008).A variety of circumstances can favor the maintenance or spread of an inversion polymorphism. The inversion may be 2010), an inversion is involved in local adaptation to Mediterranean habitats through several morphological and phenological traits, while the standard arrangement appears in a perennial ecotype from habitats with high year-round soil moisture.…”
mentioning
confidence: 99%
“…Inversion-induced LD has been reported in a variety of organisms, including humans (Bansal et al 2007), Drosophila subobscura (Munte et al 2005), and several other species (reviewed in Hoffmann and Rieseberg 2008). Strong differentiation between chromosomal arrangements (as measured by F ST ) has also been used as evidence of inversions in Drosophila (Andolfatto et al 1999;Depaulis et al 1999;Nóbrega et al 2008).…”
mentioning
confidence: 99%